Peningkatan Hasil Belajar Dan Sikap Kolaborasi Menggunakan Model PBL Berbantuan Media Audio Visual Pada Siswa Di SDK ST. MARIA 3 Malang - Sugiyo Pranoto, S.S.; Ermina Waruwu (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The situation of educational success in Indonesia is a complex issue and can be seen from various points of view. In some aspects, there has been progress, but there are still many challenges that need to be overcome. In order to advance quality education in Indonesia, the government has implemented a curriculum development policy, namely the Independent Learning Curriculum. The Independent Learning Curriculum is a curriculum with diverse intracurricular learning, where the content presented to students will be more optimal with the aim that students will have enough time to explore concepts and strengthen competencies. The Merdeka Curriculum also uses a project basis to strengthen the achievement of the Pancasila student profile. This project was developed based on a certain theme determined by the government. The Pancasila Student Profile is formed by six main dimensions, namely: Faith, noble character, and devotion to God Almighty, Independence, Cooperation, Global diversity, Critical reasoning, Creative. However, various challenges are experienced by educational practitioners in implementing this independent curriculum. One of them is regarding the use of learning models. Using the right method will influence the learning process and learning outcomes. One of them is the problem based learning model. This learning model is problem-based and learning orientation is a learning approach that focuses on students. In this model, the teacher acts as a facilitator or guide, who helps students to develop deeper understanding and relevant skills by motivating, stimulating questions, and supporting meaningful learning experiences. The aim of this research is to implement the Problem Based Learning model assisted by audio-visual media in class II Phase A of St. Catholic Elementary School. Maria III Malang can improve learning outcomes and collaborative attitudes of students; increasing the collaborative attitude of students using the Problem Based Learning model assisted by audio-visual media in class II Phase A of St, Maria III Catholic Elementary School, Malang; and the target of achieving student learning outcomes can be successful by using the Problem Based Learning model assisted by audio-visual media in class II Phase A of St. Maria III Catholic Elementary School, Malang. The type of research used is Classroom Action Research. Data collection techniques in this research used observation, interviews and documentation. The data analysis technique used consists of data reduction by selecting raw data into information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results that refer to the problem formulation. The use of the Problem Based Learning model is effective in helping to improve learning outcomes and the collaborative spirit of students on the material on the Holy Family of Nazareth and Jesus presented in the Temple of God, at Santa Maria III Catholic Elementary School, Malang.